PEMBUKTIAN ASAS KESALAHAN DALAM PUTUSAN BEBAS TERHADAP PELAKU TINDAK PIDANA PENCABULAN ANAK DIBAWAH UMUR (STUDI PUTUSAN PENGADILAN NEGERI KOTA BUMI LAMPUNG UTARA NO 51/PID.SUS/2016/PN.KBU) - Bima Sena; Mulati Mulati (Fakultas Hukum Universitas Tarumanagara, 2020)
Proof process in the trial is a series of processes that must be carried out in the trial, this process is carried out with the aim to obtain legal certainty and justice for all Indonesian people therefore in the process of proving that law enforcement must pay close attention to the stages. The process of legal protection against children who are victims of the crime of sexual abuse of minors are contained in Law Number 35 of 2014 concerning Amendment to Law Number 23 of 2002 concerning Child Protection. However, in the trial process there were several obstacles or obstacles in achieving justice, one of which occurred in the North Lampung City District Court Decision Number 51 / Pid.Sus / 2016 / PN.Kbu, based on the facts contained in the trial process of the defendant did not meet the element of error contained in the article indicted by the Public Prosecutor, so the Panel of Judges handed down the acquittal of the defendant. This proves that in the trial process there has not yet reached a sense of justice and legal certainty received by one of the parties that is carrying out legal efforts. So that the problem arises as to how to prove the principle of error towards a free verdict. The method used by researchers is normative legal research for academic purposes supported by interviews with several sources. From the results of research and discussion in the trial process there are still often obstacles to the achievement of justice for all parties, therefore the authors suggest that the Judge handle criminal acts of sexual abuse in the future to be more careful and thorough in accordance with the law in imposing criminal decisions .